Hanging Ball and Resistance Band Training in Extracurricular Volleyball Games of High School Students - Rahmat Perdana (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Extracurricular students at High School 25 Bone struggle to acquire the overhead serve, a fundamental volleyball first attack technique. Innovative training approaches are needed to improve pupils' service accuracy and strength. This study examines the effects of hanging ball and resistance band training on overhead serve skills and the effectiveness of each on extracurricular students at High School Bone. This research is a pretest-posttest group quasi-experiment. All 30 High School 25 Bone extracurricular volleyball players are studying. Total sampling was utilized to divide the sample into two groups: hanging ball training and resistance band training. A pre- and post-treatment overhead serve skill test was used. T-tests at 0.05 were used to assess data. The results of the study showed that (1) there was a significant effect of hanging ball training on overhead service skills with a calculated t-value (12.435) > t-table (2.144); (2) there was a significant effect of resistance band training on overhead service skills with a calculated t-value (11.297) > t-table (2.144); and (3) there was a significant difference in effect between the two training methods, where the calculated t-value (3.092) > t-table (2.048). Based on the comparative results, one of the methods showed more prominent effectiveness in improving service results. This study helps High School 25 Bone coaches and sports teachers choose the proper training approaches to develop basic volleyball techniques. These data should improve sports science references for youth athlete training students.